Analisis Tingkat Penerimaan Pengguna Layanan Music as a Service Berbayar dengan Metode Unifed Theory Acceptance and Use of Technology - Jonathan Cristopher; Marcelli Indriana (Universitas Multimedia Nusantara, 2018)
This study aims to determine the factors that influence the intentions of user behavior in using paid music as a service with the case studies of JOOX VIP apps. The framework of this research is UTAUT2 that has been modified by altering and adding existing constructs, perceived usefulness, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, and search cost that will influence behavioral intention.Data was obtained by questionnaires collected from 155 respondents, whom use JOOX VIP. The collected data were analyzed by using the SEM method and the results indicates that hedonic motivation, habit, and search cost as a significant determinants of user’s behavior intention to use JOOX VIP.